Femicide: Gender Violence from Argentina (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
This article first presents a clarification of the most frequently used terms on the subject of femicide and a brief historical reference to the treatment that has been culturally given to women. Violence against women is then seen as a manifestation of historically unequal power relations between women and men. Violence against women is considered to be a circle formed by direct (physical) violence, structural violence (in social structures, primarily through laws and customs) and cultural violence. This text makes reference to the current fact of femicides and the ways in which they are presented. We go on to mention the psychological and sociological explanations of gender violence and the absence of committed political decisions. It concludes with the need to reorganize the social mentality in order to achieve long-term human social coexistence, eradicating impunity in the cases presented, asserting human rights and recognizing the paradigm shift, in the political, social and cultural spheres, where the woman is constructed as a subject, capable of creating, innovating and setting the standards that are needed for the full development of her life.Key words: femicide, violence, power relationships, social mentality.